Las posibilidades para desarrollar el proceso de la evaluación ambiental estratégica en el Perú - Flores Tenorio, Pedro (2005)
Strategic Environmental Assessment (SEA) is a tool applied ever more frequently in developed countries to take on board environmental impacts in a timely way so asto impact on decision making. lt is applied mainly to megaprojects, plans, programs and policies, even though there is as yet no consensus agreement as to its definition, its methodologies or the steps required to implement it. SEA is not just an Environmental lmpact Assessment (EIA) of plans, programs and policies, since this is an instrument for which there is considerable experience and consensus as to its use, with steps such as screening and scoping of projects performed by specialists worldwide. In Peru, the EIA is normally considered to be a document that is evaluated by the environmental authority where a project is to be undertaken to ensure that it does no significant harm to the environment. In developed countries, by contrast, the EIA it is understood more as a process than a document, with public participation. Likewise, the SEA is envisaged as a process not just endingin a report. lndeed, there may be many reports, taking account critical factors, within terms of reference that are wider than those of the EIA. What is important is that it forms part of the planning process in which the implicitval use of the environment and of natural resources is not zero. The paper studies the Strategic Environmental Assessment as a way of strengthening planning procedures. lts characteristics and information needs are described in general terms, and its administrative and budgetary requirements. We conclude by looking at the real possibilities of it being applied in Peru in a variety of sectors as a voluntary process that helps generate acceptance among those involved in projects, plans, programs and policies in both the private and public sectors. lts hould be viewed more as an opportunity than an inconvenience.